(untitled) (Transport systems and technologies, 2018)
The main idea of creating a form of communication for work in the field of rail transport - is the attraction of existing innovative tools, technologies, programs that work successfully in other parts of human activity. The article deals with the features of the development of feedback form for the transportation of goods while servicing customers on the railways of Ukraine. The possible appearance of the feedback form site, as well as the question of ensuring its effective functioning, is considered. A visual layout of the site, which may have a feedback form for the transportation of goods, is developed Today customer orientation is the cornerstone of business ideology around the world due to inability to succeed in rail freight transport without establishing a full-fledged customer dialogue. A feature of the feedback form for the transportation of goods is that it has a module for face recognition mask. The task of identifying faces is extremely relevant, since compared with other means of identifying a person there is no need for direct interaction between the system and the person. The use of the feedback form in the simulation of systems involving client-centric technology is possible due to scientific and technological progress, as well as the improvement of existing systems.